Encapsulation of the natural antioxidant of sweet potato (Ipomoea batata) in biodegradable PLA nanoparticles - Guerrero, Beatriz; Corbino, Graciela Beatriz; D´Accorso, Norma Beatriz; García, Nancy L (2020)
The encapsulation of active ingredients in colloidal nanocarriers has interesting potential to be used in controlled release. In particular, it is well know the interest of the different industries, such as pharmaceutical, food and cosmetic in the encapsulation of active principles in different types of nanoparticles (NPs). The goal of this research is focused in the possibility of encapsulation of natural antioxidants in biodegradable polymer nanoparticles.